2015
DOI: 10.4028/www.scientific.net/msf.830-831.687
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Assisted Electroless Coating of Ni-B Alloy and Composites on Aluminum Alloy Substrates

Abstract: Electroless nickel coating is one of the versatile methods to improve the physical properties of aluminium alloys. The increasing demand for high corrosion resistant surface with improved performance leads to the development of poly-alloy and composite coatings with the aid of ultrasonication. In the present study Ni-B alloy and Ni-B-CeO2 composite coatings were made on 356 aluminium alloy surfaces. The variation in structural and mechanical properties of coatings formed under both ultrasonication and magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The substantial upswing in the strength is due to the presence of a titanium-nickel intermetallic compound, having higher strength. Kim et al (Kim et al, 2009) in the experimental work noticed matrix strengthening is possible by the formation of Ni-Cu based intermetallics with suitable pretreatments.…”
Section: Nickelmentioning
confidence: 86%
See 3 more Smart Citations
“…The substantial upswing in the strength is due to the presence of a titanium-nickel intermetallic compound, having higher strength. Kim et al (Kim et al, 2009) in the experimental work noticed matrix strengthening is possible by the formation of Ni-Cu based intermetallics with suitable pretreatments.…”
Section: Nickelmentioning
confidence: 86%
“…Hardness and tensile properties were improved in the outer region compared to inner regions. Jerin et al (Pancrecious et al, 2015) studied electroless Cu and Ni-B coated B 4 C particle reinforced powder metallurgy processed aluminum composites and concentrated on the phase structure and electrochemical properties. It was found that metallic coating improves compatibility, wettability, and curtails the interfacial reaction between the matrix and the reinforcement.…”
Section: Nickelmentioning
confidence: 99%
See 2 more Smart Citations